2023
DOI: 10.1111/sms.14343
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term high‐intensity interval training improves micro‐ but not macrovascular function in hypertensive patients

Abstract: This study was registered on Clini calTr ials.gov (NCT04763005).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
(121 reference statements)
0
1
0
Order By: Relevance
“…Chronically trained subjects demonstrated enhanced FMD, peak blood flow, and peak artery diameter in the femoral artery and higher skeletal muscle oxygen desaturation and reperfusion rates compared with untrained subjects, suggesting that exercise training duration might be a considerable factor in improving macro-microvascular function in human participants [10,11]. Combined aerobic and resistance exercise training improved skin blood flow in lipid metabolism outpatients, and acute high-intensity interval running and moderate-intensity interval running improved macrovascular function in the brachial artery and microvascular function in the cutaneous artery in adolescents [12], but high-intensity interval training (HIIT) elicited only the improvement of retinal microvascular function in hypertensive patients [13]. In both land-and water-based cycling ex-ercise training enhanced macrovascular function through an increase in FMD, a decrease in arterial stiffness, and elevation of plasma NO in patients with type II diabetes, but microvascular function was only improved in the water-based exercise group [14].…”
Section: Macro-and Microvascular Response To Exercise Trainingmentioning
confidence: 99%
“…Chronically trained subjects demonstrated enhanced FMD, peak blood flow, and peak artery diameter in the femoral artery and higher skeletal muscle oxygen desaturation and reperfusion rates compared with untrained subjects, suggesting that exercise training duration might be a considerable factor in improving macro-microvascular function in human participants [10,11]. Combined aerobic and resistance exercise training improved skin blood flow in lipid metabolism outpatients, and acute high-intensity interval running and moderate-intensity interval running improved macrovascular function in the brachial artery and microvascular function in the cutaneous artery in adolescents [12], but high-intensity interval training (HIIT) elicited only the improvement of retinal microvascular function in hypertensive patients [13]. In both land-and water-based cycling ex-ercise training enhanced macrovascular function through an increase in FMD, a decrease in arterial stiffness, and elevation of plasma NO in patients with type II diabetes, but microvascular function was only improved in the water-based exercise group [14].…”
Section: Macro-and Microvascular Response To Exercise Trainingmentioning
confidence: 99%
“…Therefore, by improving training capacity, the AHA offers an interval training strategy performed with acceptable loads that ensures comparable benefits to cardiorespiratory fitness (CRF) to those associated with high-intensity exercise, while reducing the probability of cardiac risk events 15 . HIIT has been recognized as an effective exercise modality and has received widespread attention from the clinical field and healthcare professionals, with some European and North American athletic teams increasingly adopting HIIT protocols in CR 17 , 18 . It has been found that HIIT not only improves mitochondrial biogenesis, insulin sensitivity, glucose regulation, high-density lipoprotein cholesterol, deep abdominal adiposity, and blood pressure more than MICT, but also has more advantages in improving skeletal muscle strength, cardiorespiratory fitness, and athletic ability 19 21 .…”
Section: Introductionmentioning
confidence: 99%